Does higher educational attainment influence functional capabilities among African Americans with Alzheimer's disease?. (31st December 2021) - Lacroix, Faina C; Adams, Larry D.; Inciute, Jovita D.; Welch, Jacob; Starks, Takiyah D.; Laux, Renee A.; Byrd, Goldie S.; Haines, Jonathan L.; Beecham, Gary W.; Cuccaro, Michael L.; Vance, Jeffery M.; Pericak‐Vance, Margaret A.; et al.
Abstract: Background: A recent study of educational attainment (EA) in African Americans (AA) demonstrated that it is associated with a decreased risk of AD, as previously described in the Non‐Hispanic White population. Several studies have also suggested that EA is a proxy for the concept of cognitive reserve (CR) or the capacity of the brains of some individuals to compensate clinically for the neurodegenerative processes of AD. If true, then EA should also be associated with other aspects of AD, including functional impairment, often measured using the Clinical Dementia Rating scale (CDR). The aim of this study is to test the hypothesis that higher EA is associated with decreased functional impairment in AA. Methods: Participants consisted of 158 AA AD cases with known years of completed education, ascertained for a genetics study of AD. Education levels were stratified into three categories:<8 years, 9‐12 years, >12 years. We used a regression model to test the association between years of education and functional impairment (composite score) with the age at onset and sex as covariates. Using the non‐memory components of the CDR: Judgment and Problem solving, Home and Hobbies, Community Involvement, and Personal Care, we formulated a composite score of 12 totaling the individual score of the 4 components. A composite score of 0 is no functional impairment and 12 equals severe functional impairment. Results: The dataset was 77.2% female with a mean age of exam of 78.8 years and a mean CDR functional composite score of 1.97 and a mean educational attainment of 11.3 years. Our results showed a significant association between education and the composite score ( ). An increase in the years of education was negatively correlated with functional impairment. Conclusion: Our data support the hypothesis that higher educational attainment is associated with reduced functional impairment. These results extend and support the concept that EA is a measure of CR in AA, extending the role of CR and EA to functional abilities. Further studies on the mechanism by which EA is protective is needed. In addition, our results suggest that EA should be considered when evaluating functional abilities in individuals thought to have AD.